Clinical characteristics and germline mutation spectrum of RB1 in Chinese patients with retinoblastoma: A dual-center study of 145 patients. (April 2021) - Chai, Peiwei; Luo, Yingxiu; Yu, Jie; Li, Yongyun; Yang, Jie; Zhuang, Ai; Fan, Jiayan; Han, Minglei; Jia, Renbing
Abstract: Retinoblastoma (Rb) is the most common primary intraocular childhood malignancy and one of the main causes of blindness in children. In China, most tumors are diagnosed at an advanced stage and have relatively poor outcomes compared to developed countries. Here, we aimed to update the clinical manifestations and RB transcriptional corepressor 1 ( RB1 ) mutation spectrum in Chinese Rb patients. Medical charts of 184 eyes in 145 Chinese Rb patients belonging to unrelated families were reviewed. Genomic DNA was isolated from peripheral blood of the patients and their parents. Mutation analysis of whole coding regions, promoter regions and flanking splice sites in the RB1 gene was performed. In addition, multiplex ligation-dependent probe amplification (MLPA) was done to detect gross aberrations. Germline RB1 mutations were observed in 37.2% (54/145) of Rb patients. RB1 -mutated patients presented with earlier age of diagnosis ( p  = 0.019), with a significantly larger proportion of bilateral cases ( p = <0.001) and secondary malignancies ( p  = 0.027) relative to those without RB1 mutations. For ocular clinical presentations, RB1 -mutated retinoblastomas presented with a larger proportion of ectropion uveae ( p  = 0.017) and iris neovascularization ( p  = 0.001). These RB1 mutations comprised of 13 (24.1%) nonsense mutation, 13 (24.1%) splicing mutations, 11 (20.4%) frameshift deletions, 11 (20.4%) gross mutations, 3 (5.6%) missense mutations, 2 (3.7%) promoter mutations and 1 (1.9%) non-frameshift deletion. In addition, 8 novel RB1 mutations were identified. These germline RB1 mutations were not related to age at diagnosis or laterality. Here, we provide a comprehensive spectrum of RB1 germline mutations in Chinese Rb patients and describe correlations between RB1 mutations and clinical presentations. Our study also provides new evidence that will inform management and genetic counselling of Rb patients and families. Highlights: We provided a comprehensive spectrum of RB1 germline mutations in Chinese Rb patients. We described correlations between RB1 mutations and clinical presentations. Our study provided new evidence that would inform management and genetic counselling of Rb patients and families.